Synthesis and Characterization of TiO2-Ni/ Coconut Coir Fiber for Photocatalysis of Methylene Blue Degradation Under Visible Light - Bella Anggreiny; Adhitiyawarman Adhitiyawarman; Anthoni Aritonang (Jurnal Kimia Riset, 2026)
The Ni²⁺-cation modified TiO₂ photocatalyst has been synthesized using the sol-gel method. Doping with metal ions into the TiO₂ lattice structure was carried out as an effort to reduce the band gap energy and shift the absorption region into the visible light range. The synthesized TiO₂-Ni photocatalyst was subsequently combined with coconut coir fibers as a floating material, commonly referred to as the floating photocatalyst method. This research aims to determine the effect of varying Ni dopant concentrations in TiO₂-Ni/coconut coir fibers on the percentage degradation of methylene blue. Based on XRD characterization, TiO₂-Ni with 1% dopant concentration produced crystals with a size of 8.48 nm and a crystallinity degree of 72.27%. UV-Vis DRS characterization showed that the smallest band gap energy was obtained from the TiO₂-Ni sample with 1% dopant concentration, namely 2.67 eV with an absorption wavelength of 464 nm. FTIR characterization of TiO₂-Ni/coconut coir fiber revealed the appearance of new peaks at wavenumbers 1402 cm⁻¹, 1877 cm⁻¹, and 2814 cm⁻¹, corresponding to –O– groups, ester groups, and –CH₂ groups. Photocatalytic activity tests showed that the higher the Ni dopant concentration, the lower the percentage degradation of methylene blue. The TiO₂-Ni/coconut coir fiber photocatalyst with 1% dopant concentration exhibited the highest degradation efficiency, with a decrease in absorbance of 73.09% after 120 minutes under visible light irradiation.